Implementation fidelity of the universal test and treat HIV intervention in eThekwini district, South Africa - Masondo, Simiso Thamsanqa (My University, 2019)
South Africa, in response to the HIV scourge, adopted UNAIDS 90-90-90 targets. In order to achieve the second 90 target, the Universal Test and Treat (UTT) was introduced. A cross sectional investigation was done to determine whether the healthcare providers in the eThekwini district clinics implemented UTT according to the policy. The study population was the healthcare providers who worked in fixed government clinics. The study was based on Carroll’s Conceptual Framework for Implementation fidelity and it focused on the adherence domain as the measure of fidelity. The adherence subdomains were coverage and content. The adherence score for all clinics was 61.6 per cent, which is lower than the target adherence score of 75 per cent. Local government clinics had a higher coverage (65%) than provincial government clinics (62%). The content score for all facilities was 59.8 per cent with local government clinics having a higher content score (63.8%) than provincial clinics (56.3%). Out of the 400 files of HIV-positive patients reviewed, 254 had a record of ART initiation resulting in a 63.5 per cent coverage score for all clinics enrolled in this study. This score was lower compared to the target score of 90 per cent. Neither provincial nor local government clinics ensured that all HIV patients benefitted from the UTT intervention. The findings in this study revealed that UTT was not implemented with fidelity by healthcare providers in the eThekwini district clinics. One of the main limitations of this study was that some elements of the UTT intervention could not be measured due to unavailability of information. There is a need for further research which includes looking at comparing the percentage of HIV-positive patients commenced on ART before and after UTT.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Epidemiology: Implementation Science, to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2019